2021
DOI: 10.31234/osf.io/ke9uf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The “Thinking Threshold”: A therapeutic concept guided by emotion regulation flexibility

Abstract: Cognitive reappraisal is an emotion regulation strategy with significant empirical support. However, it is also true that many people have difficultly using cognitive reappraisal—and any cognitive strategy that requires significant mental effort—while experiencing intense emotions. Per the tenants of emotion-regulation flexibility, we provide information on a therapeutic concept we call the “thinking threshold” which helps clients identify the level of emotional distress at which their thinking becomes impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…From the lens of emotion regulation research (Aldao et al, 2010;Naragon-Gainey et al, 2017), these skills employ distraction and intentional physiological down-regulation of emotion, suggesting they are response-focused emotion regulation strategies (Gross, 1998). It may be that these skills actually do teach people to remain engaged with their emotions in the moment by reducing distress to a more tolerable level (Veilleux, Hyde, et al, 2022). Alternatively, they may have a delayed effect on the later development of tolerance because they improve self-efficacy, as people realize they can change the trajectory of their emotion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the lens of emotion regulation research (Aldao et al, 2010;Naragon-Gainey et al, 2017), these skills employ distraction and intentional physiological down-regulation of emotion, suggesting they are response-focused emotion regulation strategies (Gross, 1998). It may be that these skills actually do teach people to remain engaged with their emotions in the moment by reducing distress to a more tolerable level (Veilleux, Hyde, et al, 2022). Alternatively, they may have a delayed effect on the later development of tolerance because they improve self-efficacy, as people realize they can change the trajectory of their emotion.…”
Section: Discussionmentioning
confidence: 99%
“…First, "resources" are meant to reflect contextual and situational features of the moment. In a recent qualitative study (Veilleux, Hyde, & Clift, 2022) people reported that they feel less capable of tolerating distress when physically drained (i.e., hungry, tired, sick), when alone or experiencing relationship conflict, or when they had significant life stressors. In addition, people noted the compounding effects of affective statedistress was reportedly easier to tolerate when the distressing situation occurred amidst an otherwise good mood, which suggests that distress intensity may be lower when buffered by pre-existing positive affect (Lerner & Keltner, 2000).…”
Section: Psychological Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-criticism may also render people less likely to use adaptive emotion regulation strategies such as problem solving or cognitive reappraisal. Considering that self-criticism coincides with (and is predicted by) heightened negative affect, it may be that people engage in self-critical thinking when they are above their "thinking threshold" (Veilleux et al, 2022) when their abilities to think in a balanced way are impaired.…”
Section: Strengths and Future Directionsmentioning
confidence: 99%